2011
DOI: 10.1128/jvi.02206-10
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Classical Swine Fever Virus Nonstructural Proteins

Abstract: Proteolytic processing of polyproteins is considered a crucial step in the life cycle of most positive-strand RNA viruses. An enhancement of NS2-3 processing has been described as a major difference between the noncytopathogenic (non-CP) and the cytopathogenic (CP) biotypes of pestiviruses. The effects of accelerated versus delayed NS2-3 processing on the maturation of the other nonstructural proteins (NSP) have never been compared. In this study, we analyzed the proteolytic processing of NSP in Classical swin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…Recently, we reported on the time-resolved hierarchy of CSFV nonstructural protein processing (18). As a prerequisite for studying the NS2-3 cleavage in virus-infected cells, a monoclonal antibody (moAb) was established that was directed against the protease domain of NS3 (GL3p1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported on the time-resolved hierarchy of CSFV nonstructural protein processing (18). As a prerequisite for studying the NS2-3 cleavage in virus-infected cells, a monoclonal antibody (moAb) was established that was directed against the protease domain of NS3 (GL3p1).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed analyses demonstrated that the availability of the cellular cofactor JIV ("Jdomain protein interacting with viral protein"; DNAJC14) restricts NS2-3 cleavage to the first hours of infection in the noncytopathogenic (ncp) biotype whereas a continuous NS2-3 cleavage takes place in the cytopathogenic (cp) biotype of BVDV (17). Elevated levels of mature NS3 led to an enhanced processing of NS4-5 precursor molecules (18) and have been linked to the accelerated RNA replication of cp BVDVs (17). In a recent study, the decisive function of the NS3 helicase for virus particle formation became evident.…”
Section: Lassical Swine Fever Virus (Csfv) Is the Causative Agent Omentioning
confidence: 99%
See 2 more Smart Citations
“…24 The single open reading frame encodes for 1 polyprotein, which is cleaved during viral maturation into 4 structural (C, E rns , E1, and E2) and 9 nonstructural (N pro , p7, NS2, NS2-3, NS3, NS4a, NS4b, NS5a, and NS5b) proteins. 7,22,24 The CSFV proteins NS3, E rns , and E2 induce antibodies on viral infection. Antibodies developed against E rns and E2 have virus-neutralizing abilities and confer protective immunity against viral infection.…”
Section: Introductionmentioning
confidence: 99%